(untitled) (Applied Biological Research, 2022)
Plant growth promoting fungi (PGPF) have received much attention in recent past due to their plant growth promoting ability and antagonistic activity against disease causing pathogens. They can suppress the pathogen directly by antagonistic mechanism or indirectly by inducing systemic resistance. The present study was aimed to assess the biocontrol efficacy of rhizospheric fungi, isolated from rice fields, against rice blight pathogen Curvularia lunata. Dual culture method was used to assess the antagonistic potential of isolates against the pathogen. Out of the 20 isolates, 14 isolates exerted positive effects against C. lunata in dual culture. SEM studies of interacting zone between the pathogen and isolates in dual culture revealed the mycoparasitic property of Trichoderma aureoviride TaN16 and Aspergillus niger AnD6 against the pathogenic fungus. These two isolates were found associated with HCN production. Three fungal isolates viz., T. aureoviride TaN16, T. yunnanense TaN17 and Talaromyces purpureogenus TpG11 triggered the induction of defense enzymes like phenylalanine ammonia-lyase, polyphenol oxidase and peroxidase. The study revealed that the rhizospheric fungal isolates having biocontrol potential can serve as alternative to chemical fungicides under integrated disease management.